EDUKASI ECO-ENZYM SEBAGAI SOLUSI MANAJEMEN PENGOLAHAN SAMPAH RUMAH TANGGA DI SMK NEGERI 7 PEKANBARU - Wardi , Jeni; Khairani, Zulia; Indarti, Indarti; Nasution, Imran Al Ucok; Saputra, Trio (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2025)
The environmental crisis, particularly related to organic waste and pollution, has become a major challenge that needs to be addressed immediately. One effective way to reduce waste volume is by processing it into beneficial products, such as eco-enzyme, a fermented liquid derived from organic waste that offers various eco-friendly benefits, including water purification and soil enrichment. Waste management education should be introduced from an early age, and universities play a crucial role in promoting this program through a structured managerial approach. Additionally, the implementation of waste management based on efficiency and sustainability can lead to the creation of environmentally friendly economic products, adding value to society. Based on this, the Community Service Team of Unilak Postgraduate Lecturers conducted a community engagement program to enhance waste management through eco-enzyme production training at SMK Negeri 7 Pekanbaru, a school committed to fostering an energy-saving culture and environmental conservation. This activity aimed to educate students on how to process organic waste into eco-enzyme, contribute to environmental preservation, and encourage the development of sustainability-based products with economic potential for the community. The results of this activity showed an improvement in students' understanding of the eco-enzyme concept, both in theory and practice. Students not only grasped the benefits of eco-enzyme in waste management but also successfully produced eco-enzyme independently through hands-on practice. Moreover, this activity fostered students' awareness of the importance of sustainable organic waste management, which is expected to be applied in their daily lives.